2021
DOI: 10.1080/1475939x.2020.1854844
|View full text |Cite
|
Sign up to set email alerts
|

‘It is no longer scary’: digital learning before and during the Covid-19 pandemic in Irish secondary schools

Abstract: The use of digital technology to support teaching and learning in schools has been rising for years, but in March 2020, it became the only option when the Covid-19 pandemic resulted in the closure of almost all educational institutions worldwide. This article reports on a survey of secondary school leaders (n = 72) in Ireland, conducted three months after the closures. Leaders' beliefs about technology, digital practices before the pandemic and responses to the emergency are considered. The findings suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 18 publications
2
62
0
3
Order By: Relevance
“…As evidenced by almost all the findings, the abrupt transition to emergency online teaching was the most direct impact of the Covid-19 pandemic on English language teaching (Moser et al, 2021;Novikov, 2020;Turchi et al, 2020). Specifically, results showed that online teaching has gained a permanent status as the preferred mode of teaching for English, even for the post-pandemic period, although it was, initially, an option to mitigate the effects of the pandemic (Andriivna et al, 2020;Karakuzu et al, 2020;Scully et al, 2021).…”
Section: Findings Of the Second Research Question Based On The Impact Of Covid-19 On English Language Teaching And Learning From The Globmentioning
confidence: 97%
“…As evidenced by almost all the findings, the abrupt transition to emergency online teaching was the most direct impact of the Covid-19 pandemic on English language teaching (Moser et al, 2021;Novikov, 2020;Turchi et al, 2020). Specifically, results showed that online teaching has gained a permanent status as the preferred mode of teaching for English, even for the post-pandemic period, although it was, initially, an option to mitigate the effects of the pandemic (Andriivna et al, 2020;Karakuzu et al, 2020;Scully et al, 2021).…”
Section: Findings Of the Second Research Question Based On The Impact Of Covid-19 On English Language Teaching And Learning From The Globmentioning
confidence: 97%
“…High-tech homes had fast broadband and access to interactive learning activities through computers, and mid-tech homes had slow or unreliable Internet, shared devices or only mobile phones to access materials and interact with their teacher and other students. Digital inequities were identified in most of the articles in this special issue and were correlated with rural-urban divides (for example, Bokayev et al, 2021;Scully et al, 2021), socio-economic context of households (for example, Greenhow et al, 2020;Scully et al, 2021) and the cultural context such as restrictions on girls' access to the Internet (Khlaif et al, 2020). The level of technology available and the educational context influenced the pedagogical practices as students learnt through prerecorded instructional videos, interactive online lessons, educational television and printed resources.…”
Section: Equity Planning For the Future And Valuing Teachersmentioning
confidence: 99%
“…The level of technology available and the educational context influenced the pedagogical practices as students learnt through prerecorded instructional videos, interactive online lessons, educational television and printed resources. Students in low-tech and low socio-economic households engaged less with learning (Scully et al, 2021). High-tech, high socio-economic households were likely to also be advantaged by correlating to parents with higher levels of education who could better support their children's learning (for example, Bokayev et al, 2021;Greenhow et al, 2020).…”
Section: Equity Planning For the Future And Valuing Teachersmentioning
confidence: 99%
See 2 more Smart Citations